2018
DOI: 10.1161/circresaha.118.313558
|View full text |Cite|
|
Sign up to set email alerts
|

Serum Bioavailable and Free 25-Hydroxyvitamin D Levels, but Not Its Total Level, Are Associated With the Risk of Mortality in Patients With Coronary Artery Disease

Abstract: Rationale: Bioavailable and free 25-hydroxyvitamin D (25(OH)D) are emerging measurements of vitamin D. Whether serum bioavailable or free 25(OH)D level is associated with mortality in patients with coronary artery disease (CAD) is unknown. Objective: Our aim is to determine the potential association between serum total, bioavailable, and free 25(OH)D levels and the risk of mortality among patients with CAD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 38 publications
1
58
0
Order By: Relevance
“…(33) In addition, bioavailable 25OHD has been suggested to be a more informative measure of vitamin D status for the prognosis of coronary artery disease than total 25OHD. (34) The nonsignificant association of free 25OHD levels with survival is unexpected in the current study. However, considering that only tiny amounts (<0.03%) of total 25OHD are free and unbound in serum, (15) bioavailable 25OHD levels are approximately equal to albumin-bound 25OHD levels.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…(33) In addition, bioavailable 25OHD has been suggested to be a more informative measure of vitamin D status for the prognosis of coronary artery disease than total 25OHD. (34) The nonsignificant association of free 25OHD levels with survival is unexpected in the current study. However, considering that only tiny amounts (<0.03%) of total 25OHD are free and unbound in serum, (15) bioavailable 25OHD levels are approximately equal to albumin-bound 25OHD levels.…”
Section: Discussionmentioning
confidence: 40%
“…Findings from epidemiological studies support this notion that bioavailable 25OHD levels were better linked to biological outcomes than the free fraction alone. (34,35) Our results highlight that bioavailable measures of 25OHD are potentially useful for predicting the risk of liver cancer mortality. With the recent availability of a commercial direct free 25OHD measurement ELISA kit, the determination of bioavailable 25OHD is much easier and more precise than the calculation based on the DBP and total 25OHD levels.…”
Section: Discussionmentioning
confidence: 78%
“…In normal subjects, the use of serum T25D which is widely available is the optimal screening test for assessment of vitamin D insufficiency and deficiency. There may be a role for the use of F25D, based on a recent study that showed F25D was more closely associated with cardiovascular mortality than with T25D; however, this result needs confirmation in other clinical outcomes studies.…”
Section: Discussionmentioning
confidence: 99%
“…In a short 12-week study of weekly 50 000 IU D2 or D3, the decrease in serum PTH at 4 weeks was more highly correlated with F25D than T25D but after 8-12 weeks of treatment this was no longer true [17]. A recent paper in 1387 Chinese patients with proven coronary disease showed that F25D, but not T25D was highly correlated with coronary disease and mortality during a 6.7-year follow-up suggesting that F25D may have an important clinical role in cardiovascular disease [18]. In a comparison of baseline physical tests of grip strength and gait speed, there were significant correlations with F25D but not T25D [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies reported that bioavailable 25(OH)vitD may be a better biomarker for vitD status. For example, free and bioavailable 25(OH)vitD levels may be useful predictors for the prognosis of patients with coronary artery disease [20]. By contrast, other studies refuted this view [21,22].…”
Section: Introductionmentioning
confidence: 99%